The Retinitis Pigmentosa-Linked Mutations in Transmembrane Helix 5 of Rhodopsin Disrupt Cellular Trafficking Regardless of Oligomerization State - Mallory, D. Paul (Biochemistry, 2018)
G protein-coupled receptors can exist as dimers and higher-order oligomers in biological membranes. The specific oligomeric assembly of these receptors is believed to play a major role in their function, and the disruption of native oligomers has been implicated in specific human pathologies. Computational predictions and biochemical analyses suggest that two molecules of rhodopsin (Rho) associate through the interactions involving its fifth trans-membrane helix (TM5). Interestingly, there are several pathogenic loss-of-function mutations within TM5 that face the lipid bilayer in a manner that could potentially influence the dimerization of Rho. Though several of these mutations are known to induce misfolding, the pathogenic defects associated with V209M and F220C Rho remain unclear. In this work, we utilized a variety of biochemical and biophysical approaches to elucidate the effects of these mutations on the dimerization, folding, trafficking, and function of Rho in relation to other pathogenic TM5 variants. Chemical cross-linking, bioluminescence energy transfer, and pulsed-interleaved excitation fluorescence cross-correlation spectroscopy experiments revealed that each of these mutants exhibits a wild type-like propensity to self-associate within the plasma membrane. However, V209M and F220C each exhibit subtle defects in cellular trafficking. Together, our results suggest that the RP pathology associated with the expression of the V209M and F220C mutants could arise from defects in folding and cellular trafficking rather than the disruption of dimerization, as has been previously proposed.